ANALISIS WACANA KRITIS “CAKNUN ANTARA KPK DAN TEROR” DI CHANNEL YOUTUBE MATA NAJWA - A‟yun Masfupah (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This study aims to explain the discourse contained in the May 4, 2019 edition of Mata Najwa with the theme "Cak Nun Between the KPK and Terror", two years after the attack on Novel Baswedan. Emha Ainun Najib as Cak Nun at the event talked about the terror that befell Novel Baswedan. Cak Nun accused the alleged mastermind behind the attack of those who claimed he cared about the issue of anti-corruption. Novel said that the assault case against him would be difficult to reveal. This study uses Van Dijk's critical discourse analysis. Van Dijk's analysis of discourse suggests the need to look at context, such as the discourse in Mata Najwa "Cak Nun Between the Corruption Eradication Commission and Terror", it is necessary to look at Indonesia's political situation and the process of disclosing the terror case. The results showed that there were several discourses developed by Mata Najwa through these shows, namely the government was slow in uncovering the terror case that befell Novel Baswedan, this shows that democracy has not been fully implemented in Indonesia and the public cares about the KPK. The state structure institution, namely the KPK, should work with the community to help each other eradicate corruption cases in Indonesia.